2017
DOI: 10.1002/slct.201601593
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of Acetaminophen Adsorbed on 2D Clusters: A First Principles Density Functional Study

Abstract: The interaction of acetaminophen (N‐acetyl‐para‐aminophenol), a prominent analgesic and antipyretic, with 2D clusters was investigated using density functional theory with inclusion of van der Waals dispersion correction. The implicit solvation model with three different solvents; water, ethanol and carbon tetrachloride were utilized to observe the trends in binding energy as a function of solvent polarity. The calculated results demonstrate that interactions are not solely dependent on solvent polarity, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…This is similar to the favorable adsorption configuration of pyrazinamide and acetaminophen on the BN surface (top-N in the references). [16][17] This AB stacking configuration results from moving the adsorbed molecule on AA site on by a BÀ N bond length along the vertical direction to the zigzag chain (Figures 2b-e). This AB site results from the surface distribution of π electrons of the h-BN layer.…”
Section: Adsorption On the H-bn Monolayermentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the favorable adsorption configuration of pyrazinamide and acetaminophen on the BN surface (top-N in the references). [16][17] This AB stacking configuration results from moving the adsorbed molecule on AA site on by a BÀ N bond length along the vertical direction to the zigzag chain (Figures 2b-e). This AB site results from the surface distribution of π electrons of the h-BN layer.…”
Section: Adsorption On the H-bn Monolayermentioning
confidence: 99%
“…[14] They have been widely applied in adsorption of gases, alkali metals and organic compounds. [15] For instances, electronic properties of acetaminophen, [16] pyrazinamide, [17] dimethyl sulfoxide [18] and DNA nucleobases [19] adsorbed on two-dimensional clusters such as graphene, BN, silicene, etc. were investigated using density functional theory.…”
Section: Introductionmentioning
confidence: 99%
“…A smaller distance between the adsorbate and absorbent often lead to a higher charge transfer between the adsorbent and the adsorbate molecules. Hence the sensitivity of the adsorbent materials towards the adsorbate molecules can be understood which plays an important role in a drug sensor device development [ 89 ]. Several studies also claimed that a smaller adsorbent-adsorbate distance leads to a stronger interaction between and provides them with higher stability [ 90 ].…”
Section: Basic Properties Investigated For Drug Delivery and Sensing mentioning
confidence: 99%
“…The phosphorene nanosheet was further investigated by U. Saikia et al to find an efficient electrochemical sensor or nano-drug delivery vehicle for acetaminophen drug or more commonly known as paracetamol [ 89 ]. It was observed that phosphorene adsorbed acetaminophen drug slightly more strongly compared to graphene with an adsorption energy of −20.99 kcal/mol and an adsorbent-adsorbate distance of 3.28 Å following by −20.06 kcal/mol and 3.13 Å for graphene.…”
Section: Miscellaneous Ldns For Drug Delivery and Sensing Applicationmentioning
confidence: 99%
“…4,18,19 Computational methods have also been used to investigate the biological responses of the BP surface 20 as well as the interaction of various drugs with this surface. [21][22][23] According to most reports, the biomolecules are physisorbed on the BP surface, with good stability, so that the structure of the adsorbed molecule is not disrupted by the adsorption process. 20,24 Adsorption of aromatic molecules has always been considered for various reasons.…”
Section: Introductionmentioning
confidence: 99%